Spatial price discrimination with online competition - Jin Guo; Yingzhi Xu (European Regional Science Association (ERSA), 2016)
Benefit from the advantage of externalities, urban agglomerations are playing more and more important roles in regional economic development. However, present literature failed to distinguish the differences between urban agglomerations' pecuniary externality and technology externality. In this paper, we took Chinese five national key construction urban agglomerations as cases to make more comprehensive empirical studies of these two types externalities' manifestations, mechanisms and key factors. The results indicated that (a) urban agglomerations' pecuniary externality manifested as inter-urban capital allocation while its technology externality manifested as inter-urban technology spillover. Currently, (b) the key factor for Chinese five national key construction urban agglomerations' pecuniary externality was market size, that meant to pursue larger market size was one main motivation in forming Chinese urban agglomerations, but the inter-urban capital allocation did not show a trend of shifting to cities with higher labor productivity. (c) The key factor for Chinese five national key construction urban agglomerations' technical externality was economical density, that meant to pursue higher economical density was another main motivation in forming Chinese urban agglomerations, but both cities' own research and development activities and the spread from other cities failed to improve urban agglomerations' technological levels. Besides, (d) there was no evidences suggested diversification or specialization of industrial structure had relations with urban agglomerations' pecuniary externality or technology externality. The regressions of dummy variables indicated that (e) there were no significant differences in pecuniary externality between Chinese five national key construction urban agglomerations' core cities and surrounding cities, but their technology externality presented complex differences.
Keywords: O47; R1; R3; 330; urban agglomeration; pecuniary externality; technology externality; agglomerate motivation